Development of a hybrid fermentation-enzymatic bioprocess for the production of ethyl lactate from dairy waste - Koutinas, Michalis; Menelaou, Maria; Nicolaou, Evrydiki (My University, 2014)
This work explores the potential for the development of a hybrid fermentation-enzymatic process for the production of ethyl lactate from dairy waste. Cheese whey was used in Kluyveromyces marxianus and Lactobacillus bulgaricus batch cultures to produce ethanol and lactic acid respectively. Subsequently, the fermentation products were transferred into an organic phase through liquid-liquid extraction and ethyl lactate was formed in an esterification reaction catalyzed by lipases. The production of ethanol and lactic acid achieved under different conditions was 23gL-1 and 29gL-1, respectively. Furthermore, the efficiency of various organic solvents for the esterification reaction was evaluated and toluene was chosen for application in the process. The effect of water content was determined aiming to maximize the product yield and 40mgml-1 was the optimal enzyme concentration. The bioprocess achieved maximum conversion of 33% constituting a valuable alternative to the application of energy demanding chemically derived methods.
Keywords: Cheese whey valorization; Ethanol; Ethyl lactate; Lactic acid; Lipase